Flipped Classrooms Implementation in Rural Area - Maulana, Danang Esha; Basikin, Basikin; Islamiaty, Dian (International Journal of Contemporary Studies in Education, 2024)
This study explored the challenges in implementing flipped classrooms learning in English language teaching and learning activity in Banjar Agung. An English language teacher and two seventh graders are interviewed in this study. Data were gathered by utilized interviews and observation. Data were analyzed by triangulation. This study revealed that the main challenges in implementing flipped classrooms are limited or out of quota cellular and internet signals that might be lost during pre-class activity. The study also revealed that the English language teacher was seldom to send or provide pre-class learning materials to their students.